Coherencia y eficacia de la acción exterior de la Unión Europea a la luz del Tratado de Lisboa: la relación entre desarrollo y seguridad - González Alonso, Luis N. (Revista Española de Desarrollo y Cooperación, 2023)
As a result of the broadening of its instruments for foreign policy, the European Union is considered to be in an optimum condition to take on a more leading role in managing one of the most important phenomena to have arrived on the panorama of international cooperation in recent years: the interaction between security and development. This is a particularly sensitive as well as attractive area to analyse from the point of view of the coherence and efficacy of the EU’s external action. In relation to this it should be asked to what extent the Lisbon Treaty can help to correct the deficiencies and difficulties manifested to date in the practice.